Efeito de um programa de exercício multicomponente em parâmetros do equilibrio e memória visuomotora em idosos - João Pedro Rodrigues da Silva Tomé de Miranda (2016)
The aim of the present study was to investigate the effects of a multicomponent training on the older adult's visuomotor memory and balance. The sample comprised 14 elderly subjects divided by convenience in two groups: a) Experimental Group (GE; n= 6; mean age=70,00±8,90 years) submitted to a 4 months Multicomponent training with 3 sessions/week an b) Control Group (n= 8; mean age=70,50± 5,20 years) with a ludic and light physical activity session a week. The evaluation test on the visuomotor memory from Thinus-Blanc et al. (1996) and the evaluation test on balance from Tinetti (1986) were applied to all the subjects before and after the physical exercise program. Our results showed: i) No statistical differences between groups on visuomotor memory percentage of change after 4 months. However, while the CG significantly worsened from the 1st moment to the 2nd moment of evaluation, there were no significant changes in EG; ii) Statistical differences between groups on balance (total, static, dynamic) percentage of change after 4 months were detected. It was possible to observe a significant decline in total and static balance on CG and a significant improvement in EG. The results suggest that a multicomponent exercise program can significantly improve balance. However, it was not of sufficient duration, intensity or specificity to induce significant changes on the visuomotor memory capacity.